Developing, Piloting and Scaling-up of Nepal’s Neonatal Care Program - Poudel, D C; Acharya, B; Pant, S; Poudel, D; Pradhan, Y V (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The Community-based Newborn Care Package is a set of neonatal care interventions to be delivered through the existing government system of facility-based health workers and community based volunteers in Nepal. The package was developed by the government of Nepal in 2007 based on the evidence from Nepal and neighboring countries and designed to be implemented as a comprehensive package to improve newborn survival. This paper reviews the process, progress, and lessons learned from the program design, early-implementation and monitoring and provides future directives to improve upon this integrated package that uses a continuum of care approach from the pre-pregnancy to neonatal periods by involving the communities, health workers and the private sector. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords: Community-Based Neonatal Care Package; integrated package; Female Community Health Volunteer; neonatal mortality; Nepal.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>